Unveiling the knowledge domain and emerging trends of olfactory dysfunction with depression or anxiety: A bibliometrics study - Zhou, Fangwei; Zhang, Tian; Jin, Ying; Ma, Yifei; Li, Yangsong; Zeng, Mengting; Yu, Guodong (Frontiers in Neuroscience, 2022)
Olfactory dysfunction (OD) accompanied by depression or anxiety is a very common clinical problem, and there has been a growing number of studies on OD with depression or anxiety in recent decades. This study performed bibliometric and visual analyses of the literature on OD with depression or anxiety to derive research trends and identify emerging research foci. Relevant publications were obtained from the Science Citation Index-Expanded and Social Sciences Citation Index in the Web of Science Core Collection databases (2002-2021). CiteSpace and VOSviewer were applied to identify and evaluate research foci and emerging trends in this research domain. The analyses found the number of publications related to OD with depression or anxiety has increased significantly over the past 20 years, up from 15 in 2002 to 114 in 2022. The country that ranked highest in the quantity of articles and international cooperation was the USA. The Top 10 most frequent keywords were “depression,” “olfaction,” “anxiety,” “dysfunction,” “olfactory bulbectomy,” “olfactory dysfunction,” “Parkinson’s disease,” “odor identification,” “brain,” and “disorders.” Analysis of keywords with the strongest citation bursts revealed that "oxidative stress" is an emerging research hotspot. A timeline chart of the cluster of co-cited references demonstrated that Parkinson’s disease was always a topic of interest in this area of research. This study conducted an objective, comprehensive, and systematic analysis of these publications, and identified the development of trends and hotspots in this research domain. It is hoped that this work will provide scholars, worldwide, with information to assist them in further research and the development of new therapies.